Peranan Pengembangan Sumber Daya Manusia Dan Pelatihan Dalam Meningkatkan Kinerja Karyawan Pada CV Geprek Jon X Papa Risol - Khoirun Nisa; Ahmad Syihabuddin A.F; Frida Aprilia; Ayu Lucy Larassaty (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
Human resources are the driving force for the organization. HR needs to be developed in order to provide good results for the company. Therefore HR development is very necessary because it has important aspects for increasing HR productivity and also has certain goals that must be achieved for the advancement of a company or social service organization. This study aims to determine the role of HR development and training in improving employee performance. This study uses an associative method with a quantitative approach. The sample of this research is employees at CV Geprek Jon X Papa Risol. By using purposive sampling technique and obtained 100 respondents. Data analysis using multiple linear regression. The results of this study indicate that HR Development (X1) has a positive and significant role on Employee Performance (Y) and Training (X2) has a positive and significant role on Employee Performance (Y). Another result, that together HR development and training have a positive and significant impact on employee performance